2008
DOI: 10.1038/sj.bjc.6604451
|View full text |Cite
|
Sign up to set email alerts
|

Clinical interest of KRAS mutation detection in blood for anti-EGFR therapies in metastatic colorectal cancer

Abstract: a series of 59 metastatic colorectal cancer (MCRC) patients treated with cetuximab-based chemotherapy (CT), that KRAS mutation was highly predictive of treatment resistance and that progression-free survival was significantly increased in wild-type KRAS compared with mutant KRAS patients (Di Fiore et al, 2007). All the studies published so far have unambiguously confirmed that the presence of somatic KRAS mutation is indeed highly predictive of resistance to anti-EGFR antibodies in MCRC patients (Lièvre et al,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 9 publications
2
28
0
2
Order By: Relevance
“…Moreover, considering the difficulty in obtaining metastatic tissue, at least in certain patients, analyses on blood samples should be of significant clinical interest. 26 Our study illustrates that different mechanisms can lead to artefactual mutations, as previously reported. 13,17,27 First, these artefacts have been reported when PCR amplification is performed on low amounts of DNA: a nucleotide misincorporation occurring during the first cycle of PCR will then be homogeneously carried by all PCR molecules generated during subsequent cycles.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, considering the difficulty in obtaining metastatic tissue, at least in certain patients, analyses on blood samples should be of significant clinical interest. 26 Our study illustrates that different mechanisms can lead to artefactual mutations, as previously reported. 13,17,27 First, these artefacts have been reported when PCR amplification is performed on low amounts of DNA: a nucleotide misincorporation occurring during the first cycle of PCR will then be homogeneously carried by all PCR molecules generated during subsequent cycles.…”
Section: Discussionsupporting
confidence: 80%
“…Some authors have shown that detection of KRAS mutations in the peripheral blood of mCRC patients is possible by the development of combining tests indicating in blood, first the presence of tumour DNA (circulating tumours cells), then KRAS status, with a highly significant correlation to KRAS mutations in tumours (Di Fiore et al, 2008;Yen et al, 2009). Moreover, it was reported in a series of 76 patients that those with KRAS wild-type circulating tumour cells had a better progression-free and overall survival when treated with cetuximab plus chemotherapy (Po0.0001) (Yen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] These therapies are exclusively effective in tumors with wild-type KRAS. [10][11][12][13] In colorectal cancer patients, in particular, KRAS mutation testing has quickly become standard-of-care. 14 In the era of targeted therapy and personalized medicine, requests for KRAS mutation testing will increase, and are likely to do so exponentially.…”
mentioning
confidence: 99%